The Cambridge companion to Martin Luther - McKim, Donald K. 1950- (Cambridge [u.a.] Cambridge Univ. Press, 2003)
Martin Luther (1483–1546) stands as one of the giant figures in history. His activities, writings, and legacy have had a huge effect on the western world. This Cambridge Companion provides an accessible introduction to Martin Luther for students of theology and history and for others interested in the life, work and thought of the first great Protestant reformer. The book contains eighteen chapters by an international array of major Luther scholars. Historians and theologians join here to present a full picture of Luther's contexts, the major themes in his writings, and the ways in which his ideas spread and have continuing importance today. Each chapter serves as a guide to its topic and provides further reading for additional study. The Companion will assist those with little or no background in Luther studies, while teachers and Luther specialists will find this accessible volume an invaluable aid to their work.
Includes bibliographical references (p. 304 - 312) and index
Online-Ausg.
Keywords: Luther, Martin -- 1483-1546; Luther, Martin ; 1483-1546; Aufsatzsammlung